2012
DOI: 10.1186/1471-2407-12-288
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for consolidative radiotherapy in the treatment of aggressive and localized Non-Hodgkin Lymphoma? A systematic review with meta-analysis

Abstract: Background Chemotherapy is the mainstay of non-Hodgkin lymphoma (NHL) treatment. Based on expert opinion, the use of radiotherapy (RT) is currently preferred in some institutions as consolidative treatment for patients with localized disease. The lack of conclusive data coming from conflicting studies about the impact of treatment demands a systematic review, which could provide the most reliable assessment for clinical decision-making. We evaluate the addition of RT post-CT, for aggressive and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
0
10
0
1
Order By: Relevance
“…Although there is controversy regarding the consolidative role of RT, several studies have shown that the addition of RT to chemotherapy improves PFS for patients with NHL [7-9,11]. Laskar et al [13] demonstrated that disease-free survival (DFS) and OS rates are higher in patients treated with chemotherapy combined with RT than in those treated with chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is controversy regarding the consolidative role of RT, several studies have shown that the addition of RT to chemotherapy improves PFS for patients with NHL [7-9,11]. Laskar et al [13] demonstrated that disease-free survival (DFS) and OS rates are higher in patients treated with chemotherapy combined with RT than in those treated with chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that RT prolongs progression-free survival (PFS) [8,9]. However, in long-term follow-up studies involving the use of rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP), the role of RT requires clarification [10-12].…”
Section: Introductionmentioning
confidence: 99%
“… 17 – 20 A systematic review conducted by Santos et al showed that radiation could enhance progression-free survival after chemotherapy. 21 Therefore, since nodal DLBCL and PG-DLBCL share many of the same biological characteristics, systemic chemotherapy followed by radiotherapy is now the preferred treatment for PG-DLBCL in certain centers. Evidence from retrospective data also confirmed that the addition of radiation significantly reduced the local relapse rate compared with chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is considered if there is bulky disease at presentation. For aggressive localized NHL, the addition of radiotherapy postchemotherapy does not seem to offer any benefit in progression free or overall survival [3].…”
Section: Discussionmentioning
confidence: 99%